(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Manju Kapur is a famous Indian English novelist whose writings reflect man– woman relationship, human desire, longing body, gender discrimination, marginalization, rebellion and protest. The present paper will highlight a woman’s struggle for her autonomy and quest for her identity in a patriarchal society. Kapur adopts to scrutinize the problems besetting the Indian woman. The issue of gender discrimination revolves around the life of the female protagonists Veermati, in The Difficult Daughters, Astha, in A Married Woman Nina in The Immigrant respectively. They are suppressed by their families because of their efforts to prove their identities. The comparisons of ideas between the male and the female regarding the differences in freedom, autonomy self-identity and gender disparity are the main issues discussed in this paper with the analysis of the female protagonists.Her novels manifest women’s struggle for emancipation from economic, political and social bondages. The present paper also focuses on the role of women in traditional families oppressed under the patriarchal or cultural restraints. Manju Kapoor’s perception of women’s liberation and autonomy are deeply entrenched within the socio-cultural and economic spaces. They challenge the male domination and patriarchal mechanisms of surveillance and control over women’s body. The three protagonists struggle, for self- existence in this vast universe. They are the true representatives of oppression which women are facing in the world today. Kapur’s works project the transgression of a silent and a submissive woman to an assertive, awakened and an empowered woman, who gradually defy patriarchal norms.